Predicting Potential Distribution of Teinopalpus aureus Integrated Multiple Factors and Its Threatened Status Assessment - Congcong Du; Xueyu Feng; Zhilin Chen; Gexia Qiao (Insects)
The accurate prediction of the niche and the potential distribution of a species is a fundamental and key content for biodiversity related research in ecology and biogeography, especially for protected species. Biotic interactions have a significant impact on species distribution but are often overlooked by SDMs. Therefore, it is crucial to incorporate biotic interaction factors into SDMs to improve their predictive performance. The Teinopalpus aureus Mell, 1923 is endemic to high altitudes in southern East Asia, renowned for its exceptional beauty and rarity. Despite the significant conservation value, its spatial distribution remains unclear. This study integrated climate data, host plants, and empirical expert maps to predict its potential distribution. The results indicated that utilizing the species richness of host plants as a surrogate for biotic interactions was a simple and effective way to significantly improve the predictive performance of the SDMs. The current suitable distribution of T. aureus and its host plants is highly fragmented, primarily concentrated in the Nanling and Wuyi Mountains, and consisting of numerous isolated small populations. Given climate change, their distribution is significantly shrinking, increasing the threatened level in the future. Especially for the population of T. aureus hainani Lee, the likelihood of extinction is extremely high. Abiotic factors not only directly affect the distribution of T. aureus but also indirectly impact it through the host plants. This was evident in the delayed response of T. aureus to climate change compared to its host plants, which is called the “hysteresis effect” caused by biotic interactions. Overall, we tentatively suggest regarding T. aureus as a vulnerable species. In the future, multiple measures could be taken to indirectly protect the feeding and habitat resources of T. aureus by conserving host plants, thereby enhancing its survival prospects.